Modelling the impacts of cover crops on soil C stocks and N dynamics using Daisy: Model evaluation and scenario analysis - Grønning, Celine Rendboe; Jensen, Lars Stoumann; Engedal, Tine; Andersen, Maria Skovgaard; Hansen, Veronika; Rashid, Muhammed Adil; Schwartzkopff, Magdalena Vinkler; Svane, Simon Fiil (Agricultural systems, 2025)
Agroecosystem models can be useful tools for investigating the environmental and climatic impact of varying agricultural management practices. These include using cover crops (CC) to reduce nutrient leaching or prevent soil erosion. However, the application of models with longer timescales and varying system conditions requires them to be well-calibrated and tested. This study aimed to improve the ability of the Daisy model to simulate CC dynamics, focusing on aboveground and belowground (root) growth, biomass production and allocation, and carbon (C) and nitrogen (N) dynamics. Oilseed radish (OR), winter rye (WR) and hairy vetch (HV) were the CC species studied. The cover crop sub-models were calibrated using two years of experimental field data from a sandy soil, and evaluated against one year of similar data from a loamy soil. The calibrated CC models were then applied in realistic crop rotation scenarios. In the calibration and evaluation, the models showed a good fit between observed and simulated values, with some deviations where the model could not account for the varying environmental conditions. The scenario analysis showed that CCs can have a significant impact on soil C stocks and N leaching. The study concluded that CCs could mitigate the negative environmental impacts of agriculture by reducing N leaching and contributing to soil C sequestration, with WR having a slightly greater effect on soil C stock change and OR a greater effect on N leaching reduction. The findings support the use of CCs in sustainable agriculture and the application of the Daisy model as a tool for evaluating their impact on the mitigation of climate change and on the environment. [Display omitted]